Recent progress in the use of ‘omics technologies in brassicaceous vegetables - Witzel, Katja; Neugart, Susanne; Ruppel, Silke; Schreiner, Monika; Wiesner, Melanie; Baldermann, Susanne (Frontiers in Plant Science, 2015)
Continuing advances in 'omics methodologies and instrumentation is enhancing the under-standing of how plants cope with the dynamic nature of their growing environment. 'Omics platforms have been only recently extended to cover horticultural crop species. Many of the most widely cultivated vegetable crops belong to the genus Brassica: these include plants grown for their root (turnip, rutabaga/swede), their swollen stem base (kohlrabi), their leaves (cabbage, kale, pak choi) and their inflorescence (cauliflower, broccoli).Characterization at the genome, transcript, protein and metabolite levels has illustrated the complexity of the cellular response to a whole series of environmental stresses, including nutrient deficiency, pathogen attack, heavy metal toxicity, cold acclimation, and excessive and sub-optimal irradiation. This review covers recent applications of 'omics technologies to the brassicaceous vegetables, and discusses future scenarios in achieving improvements in crop end-use quality.